RNA Regulatory Elements and Polyadenylation in Plants - Hunt, Arthur G. (Frontiers in Plant Science, 2012)
Alternative poly(A) site choice (also known as alternative polyadenylation, or APA) has the potential to affect gene expression in qualitative and quantitative ways. Alternative polyadenylation may affect as many as 82% of all expressed genes in a plant. The consequences of APA include the generation of transcripts with differing 3’-UTRs (and thus differing potential regulatory potential) and of transcripts with differing protein-coding potential. Genome-wide studies of possible APA suggest a linkage with pre-mRNA splicing, and indicate a coincidence of and perhaps cooperation between RNA regulatory elements that affect splicing efficiency and the recognition of novel intronic poly(A) sites. These studies also raise the possibility of the existence of a novel class of polyadenylation-related cis elements that are distinct from the well-characterized plant polyadenylation signal. Many potential APA events, however, have not been associated with identifiable cis elements. The present state of the field reveals a broad scope of APA, and also numerous opportunities for research into mechanisms that govern both choice and regulation of poly(A) sites in plants.